PROVISION OF OBSERVABILITY AND CONTROLLABILITY OF COMPLEX TECHNICAL SYSTEMS UNDER THE CONDITIONS OF RECEIVING COMMANDS WITH A LARGE COMPONENT OF DISTORTION UNDER DIFFICULT AND IRREGULAR SITUATIONS - E. P. Grabchak; V. V. Grigoriev; E. L. Loginov (Современная наука и инновации, 2022)
The article deals with the problem of development of the automated system of monitoring and control of the technical conditions of complex technical systems (NPP and TPP).